Breeder’s rights and public research sector - Velho, Paulo (Science & Technology Journals, 1992)
Some eventual impacts that future legislation on intellectual property for plant breeders could have upon genetic improvement activicy, particularly that of public sector, are discussed. Starting from a rapid analysis of the social work division of breeding between public and private sectors, which present distinct and characteristic "ethos", the article goes on to analyze the importance and convenience of keeping the public sector as a counterpoint to the private sector in the terminal phase of breeding research, i. e., the liberation of new cultivars to the producer. The conclusion indicates the necessity of searching for mechanisms that guarantee the survival and strength of public research, for understanding that the preservation of autonomous public capacity in developing new technologies to meet the actual needs o f local producers is the legitimate aim of a social policy.